(untitled) (Estudios Sociales, 2020)
This article analyzes how today’s historians know that the knowledge they produce is no more than one of the modalities of the relationship that societies maintain with the past. The memory, either collective or individual, the fiction works, or at least some of them, also send us back to the past- sometimes in a more powerful way than the history books establish. Throughout the thoughts of great authors like Paul Ricoeur and Michel de Certeau, among others, we go through a path that allows us to identify the narrative or rhetorical relationships between fiction and history. This reminds us that the specificity of history, as part of the social and human sciences, is its capability to distinguish and articulate the different moments that seem contemporary in each historical period. In an age when our relationship with the past in threatened by the strong temptation of creating imagined or imaginary stories, the reflection about the conditions that permit to sustain a historical discourse- as an appropriate representation and explanation that fits the reality that once was- is fundamental and urgent.